What we know about oral collagen supplementation for skin health - a literature review - Słupczyńska, Aleksandra; Gorczyca, Kamila; Artykiewicz, Klaudia; Urbaś, Weronika; Podgórska, Klaudia; Puła, Aleksandra; Czarkowski, Marcin; Kozieł, Paweł; Grodkiewicz, Maria; Krzysiek, Urszula (Journal of Education, Health and Sport, 2022)
ABSTRACT Introduction: The efforts to restore lost collagen, regain youthful-looking skin and healthier joints have made collagen oral supplements a huge trend of the last few years. Because collagen is the main building protein of our body, many people may ask themselves - can collagen supplementation have a real impact on our health? Are these nutraceuticals a fountain of youth in a bottle or nothing more than marketing hype? The aim of the study: The aim of this paper was to present the current state of knowledge on the supplementation of collagen and application of collagen in oral nutraceuticals. Material and methods: Literature review available on PubMed, Science Direct and Google Scholar and evaluation of available randomized controlled trials using collagen supplementation in terms of treatment effectiveness in terms of skin quality, anti-aging benefits and potential use in dermatology. Abstracts, comments, and non-English language articles were excluded. Conclusions: Collagen is important for maintaining the structural integrity of every tissue in the body. Despite many studies on collagen supplementation, the literature is still impecunious, but the scientific works so far confirm that supplementation with hydrolyzed collagen can improve various aspects of skin aging. Key words: collagen, collagen peptides, antiaging, skin health, nutraceuticals